PENGARUH KREDIBILITAS ENDORSER TERHADAP MINAT BELI DENGAN TIGA TIPE KONSUMEN PADA INDUSTRI BUSANA MUSLIMAH - Ayu Ningsetya Mardika Riskhi; Jono M Munandar; Mukhamad Najib (Universitas Mercu Buana, 2018)
Endorser credibility is one of factors which influence muslim fashion development. In the other hand, it is the challenge for Indonesia is to be a centre of muslim fashion in the world. The purpose of this study was to analyze the effect of endorser credibility on purchase intention with three types consumers. A technique of sampling method in this research was quota purposive sampling. Total sample size was 225 respondents from each 75 housewives, 75 employees, and 75 female students. Data were analyzed using descriptive statistic and SEM with PLS Approach. The results of this study shows that the credibility endorser have significant effect on purchase intention to female students. While the brand credibility and advertising credibility partially have no significant effect on purchase intention. On the type consumer housewives and employees partially have no significant effect on purchase intention. Simultaneously, advertising credibility and brand credibility affect significantly on purchase intention